2019
DOI: 10.1186/s12879-019-4316-5
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin and fetuin-A dyad for the diagnosis of proven sepsis in preterm neonates

Abstract: Background Diagnosis is the most strenuous step in the evaluation of neonatal sepsis. No gold standard diagnostic method is available except for blood culture. We aimed to investigate the role of positive and negative acute phase reactants, namely presepsin and fetuin-A, in the diagnosis of culture-proven late-onset sepsis. Methods A prospective, case-control study with the infants ≤32 weeks of age with a diagnosis of culture-proven late-onset sepsis was designed. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 30 publications
1
30
1
2
Order By: Relevance
“…After being released from the cell surface, sCD14 is cleaved by the bacterial lysosomal enzyme into an N-terminal peptide of 64 amino acids, which is then called presepsin or sCD14-ST. 12 Increased presepsin level in the circulating blood reflects the severity of bacteremia, and is therefore a reliable diagnostic and prognostic marker of neonatal sepsis. 13 In the present study, we found an optimal presepsin cut-off value of 1057 ng/mL. At this value, an AUC of 0.804 was obtained, with a sensitivity of 60.71% and a specificity of 88.24% to predict mortality within seven days.…”
Section: Discussionsupporting
confidence: 56%
“…After being released from the cell surface, sCD14 is cleaved by the bacterial lysosomal enzyme into an N-terminal peptide of 64 amino acids, which is then called presepsin or sCD14-ST. 12 Increased presepsin level in the circulating blood reflects the severity of bacteremia, and is therefore a reliable diagnostic and prognostic marker of neonatal sepsis. 13 In the present study, we found an optimal presepsin cut-off value of 1057 ng/mL. At this value, an AUC of 0.804 was obtained, with a sensitivity of 60.71% and a specificity of 88.24% to predict mortality within seven days.…”
Section: Discussionsupporting
confidence: 56%
“…In 2019, Değirmencioğlu et al investigated presepsin, comparing it to fetuin-A dyad. While most of the studies on fetuin fetuin-A have been done on animals, the authors felt it important to compare it to presepsin because it showed a valid connection to sepsis -- its levels declining in early sepsis and then increasing at 72 hrs of inflammation [ 16 ]. It is postulated that fetuin-A plays a role in the immune system by inhibiting the release of late mediators of inflammation.…”
Section: Reviewmentioning
confidence: 99%
“…In contrast, fetuin-A levels were similar in both groups, suggesting it was not useful as a diagnostic marker. Overall, using a cut-off value of 823 ng/ml, the presepsin was found to have 88.9% sensitivity and 88.9% specificity [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly high performance of presepsin was demonstrated in individual studies by Montaldo and co-workers [79], with an AUC of 0.97, and Xian and colleagues [80], who reported an AUC of 0.942. A recent study by Deǧirmencioǧlu and co-workers [81] calculated an AUC of 0.939 for the diagnosis of late-onset sepsis in preterm neonates, which was slightly outperformed by IL-6 (AUC of 0.959). This was in contrast with the findings of Ahmed and co-workers [60] who found that presepsin was superior to IL-6 (AUCs of 0.934 and 0.751, respectively), although their study was focused on the diagnosis of early-onset sepsis.…”
Section: Neonatesmentioning
confidence: 98%